Análise de vias sinalizadoras celulares como potenciais alvos antivirais: papel exercido no ciclo de multiplicação do vírus da encefalite de Saint Louis (SLEV) - Mara Camila Arantes Marques de Aguiar (2017)
Saint Louis Viral Encephalitis is an acute febrile infectious disease caused by Saint Louis Encephalitis virus (SLEV), a member of the genus Flavivirus (Flaviviridae family). Human infection with SLEV virus usually results in an asymptomatic disease presenting spontaneous resolution, but among patients developing central nervous system (CNS) syndrome, encephalitis is more common, followed by aseptic meningitis and febrile headache. The disease is endemic in the United States, but cases also occur, less frequently, in South and Central America. Likewise other Flavirus infections, there is still no effective treatment against SLEV. Recent studies conducted by the Signal Transduction Group / LabVirus / ICB / UFMG, both in vitro and in vivo, have demonstrated the potential anti-poxviral, anti-YFV and anti-DENV action of some inhibitors, particularly the cellular signal pathways involving the MAPKs (mitogen-activated protein kinases) and, specifically, MEK / ERK. These pathways participate in the regulation of virtually all cellular processes and may be required by viruses during their multiplication cycles. The aim of this study was to investigate the possible antiviral action against SLEV of pharmacological inhibitors that affect MEK / ERK and Src / Abl family tyrosine kinases both in vitro and in vivo. It was found that treatment of BHK-21 cells with Src and MEK / ERK IFs promoted a significant reduction in the SLEV viral titre (= or > 1 log) and these inhibitors act at distinct steps of viral multiplication. However, in the in vivo tests, none of the IFs (Src and MEK / ERK) was able to promote the protection of the animals or to reduce significantly the viral load after infection with the SLEV. Possibly, theineffectiveness of these inhibitors may be related to SLEV neurotrophism, since treatment with one of the MEK/ERK IFs, which exhibits antiviral action against DENV in vivo, also failed to show efficacy against SLEV. Therefore, it is also necessary to evaluate whether the IFs are able to cross the BBB in satisfactory concentrations to exert the antiviral activity against SLEV, observed in vitro.